Quality control of guava leaf (Psidium guajava L.) (Research, Society and Development, 2023)
The guava leaf (Psidium guajava L) is widely distributed in tropical regions, its composition rich in secondary metabolites has been routinely used for different therapeutic and prophylactic purposes, making quality assessment essential to ensure the effectiveness and safety of the product. use of leaves. Thus, the objective of this work is to evaluate the physical-chemical characteristics for identification and classification of purity using the methodology of characterization of structures: organoleptic, foreign material, moisture content and phytochemical analysis. The results show discrepancies between the organoleptic characteristics of the leaves studied, with healthy leaves and diseased leaves being observed with microbiological contaminants and dirt exceeding the acceptable limit for consumption patterns, also indicating that there was contamination and/or inadequate handling at a certain stage of leaf processing. negatively affecting the product. It was also identified the need for control during the packaging process of herbal medicines sold in open markets, despite the fact that the chemical constituents and moisture content are in accordance with the pharmacopoeia. Therefore, meticulous control from the collection to the availability of the product is of paramount importance so that the user can make the most of the phytotherapeutic benefits of the guava leaf (Psidium guajava L).